Analisis Penggunaan Lego dalam Pembelajaran Sejarah Perang Kusamba untuk Anak Usia Dini - Putra, I Nyoman Agus Suarya; Nugraha, Putu Gede Surya Cipta; Wardani, Ni Wayan (Institut Bisnis dan Teknologi Indonesia, 2024)
There is limited research that combines three things, namely, early childhood, technology and local wisdom. Current conventional education requires digital-based technology with all its advantages. Historical knowledge is best instilled as knowledge in early childhood in the age range of 4-6 years. The knowledge taken in this research is knowledge from a hero statue located in Kusamba village in the form of a woman holding a palm leaf named I Dewa Agung Istri Kanya. This research aims as an educational tool. Through the means of animated films, the Lego game is hoped to be able to provide historical education and be able to become a visual attraction in the educational process. The method in this research is a descriptive qualitative method by visualizing illustrations of historical toy stories of heroes that are close to children's tastes. Next, exploration and experimentation were carried out on the work by designing Lego with Balinese characters and clothing and creating the setting at the scene, namely Goa Lawah and Puri Klungkung. The production technique uses stop motion techniques. The process of making an animated film is carried out in three stages, namely pre-production, production, and post-production. Testing was carried out on material experts and media experts as well as parents who educate children aged 4-6 years. The results of 87% of respondents stated that it was suitable as a learning medium. The results of anecdotal notes on a sample of young children showed an increase in knowledge from not yet developing to developing according to expectations.